2020
DOI: 10.1016/j.amsu.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of simultaneous laparoscopic colorectal surgery and liver resection for colorectal cancer with synchronous liver metastases: Retrospective case-matched study

Abstract: Introduction Laparoscopic surgery for colorectal cancer and liver tumors are accepted as alternative procedure to open surgery. However, few studies reported outcomes of simultaneous laparoscopic surgery of these two procedures. The aim of this study was to compare short-term outcomes between laparoscopic and open approach. Materials and methods Between June 2010 to December 2019, simultaneous laparoscopic cases were retrospectively matched (1:2) to open cases. Peri-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
8
0
2
Order By: Relevance
“…A total of 2,534 unique studies were identified, of which 13 studies (between 2011 and 2021) fulfilled the inclusion criteria and were included in the study (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2,534 unique studies were identified, of which 13 studies (between 2011 and 2021) fulfilled the inclusion criteria and were included in the study (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis study based on 13 studies included 1,181 subjects with colorectal cancer and synchronous colorectal liver metastases at the start of the study; 425 of them were using minimally invasive surgery and 756 were open surgery (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Minimally invasive surgery in subjects with colorectal cancer and synchronous colorectal liver metastases was significantly related to longer operation time, less blood loss, less blood transfusion needs, shorter length of hospital stay, lower overall complications, higher overall survival, and higher disease-free survival compared to open surgery (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports assessed the short-term outcome of hepatic and colorectal SLR showing a similar or inferior blood loss, a similar or lower complication rate, and an important reduction of hospital stay for laparoscopic surgery respect to open surgery. On the contrary, longer operating times of laparoscopic surgery are generally reported (34,(50)(51)(52)(53)(54)(55)(56) even though in some referral centers shorter operative times are also registered (57,58). The long-term outcomes are also comparable with the previously described cases of abdominal metastases especially at port sites (59,60).…”
Section: Discussionsupporting
confidence: 63%
“…С развитием технического оснащения в хирургию стали активно внедрять лапароскопичес кий способ хирургического вмешательства, выделив такие преимущества, как ранняя активизация больного, уменьшение травмы и стресса [10][11][12]. В настоящее время нет однозначного мнения о превосходстве непосредственных и отдаленных результатов симультанных лапароскопических операций.…”
Section: вве де ниеunclassified